Management of Internal Haemorrhoids: A Homoeopathic Case Report (Homoeopathy for All, 2025)
Haemorrhoids, a common and often  distressing condition, involve the  swelling and inflammation of the  veins in the rectal area. Conventional  treatments primarily focus on  symptom relief, such as pain  management, reducing swelling,  and controlling bleeding.[1]  Internal Haemorrhoids, are  dilated vascular structures within the  rectal mucosa that often present with  painless rectal bleeding, prolapse, or  a sensation of incomplete evacuation.  Unlike external Haemorrhoids, they  may go unnoticed until bleeding  or prolapse occurs. Homeopathy  offers a non-invasive, holistic, and  individualized approach, addressing  the root cause rather than merely  suppressing symptoms. According to 6th edition of  organon of medicine cure as “the  highest ideal of cure is rapid gentle  and permanent restoration of health,  or removal and annihilation of disease  in its whole extended in shortest  most reliable and most harmless way  on easily comprehensible principle”.  In aphorism 186 (5th edition) Dr  Hahnemann wrote about suppressive  measures (like surgical removal or  tropical treatment) that can drive  the disease inward, causing deeper  chronic problems. [6]
Keywords: Conventional treatments; restoration of health; easily comprehensible principle; outpatient department (OPD)